Land Use Predictions to the Response of Kediri Airport - Imadudina, Annisaa Hammidah; Widodo, Widiyanto Hari Subagyo; Hidayati, Agustina Nurul (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2022)
Kediri Regency is a district with sufficient development with the existence of PSN for the construction of Kediri Airport. Kediri Airport was finally designated as PSN. This Rp 10 trillion airport is included in PSN in accordance with Presidential Regulation Number 56 of 2018. After Kediri Airport, Immediately Build the Kertosono-Tulungagung Toll Road. Land Acquisition for the Kediri Section is Completed in 2021. With this national strategic project, investment development in Kediri Regency will definitely increase. Based on the above, it is very necessary to predict future land use to be able to know the response of land use to the integrated airport and toll road project. The methods used in this research are remote sensing, GIS analysis, cellular automata analysis and descriptive analysis. Knowing the spatial response will be a very meaningful input for planners, especially in formulating plans to maximize the multiplier effect caused by the airport and toll roads on the surrounding space.